Beta-lactamase detection in Staphylococcus aureus and coagulase-negative Staphylococcus isolated from bovine mastitis - Robles, Bruno F. [UNESP]; Nóbrega, Diego B. [UNESP]; Guimarães, Felipe F. [UNESP]; Wanderley, Guido G. [UNESP]; Langoni, Hélio [UNESP] (Colégio Brasileiro de Patologia Animal - CBPA, 2014)
The objectives of the study were to evaluate the presence/production of beta-lactamases by both phenotypic and genotypic methods, verify whether results are dependent of bacteria type (Staphylococcus aureus versus coagulase-negative Staphylococcus - CNS) and verify the agreement between tests. A total of 200 bacteria samples from 21 different herds were enrolled, being 100 CNS and 100 S. aureus. Beta-lactamase presence/detection was performed by different tests (PCR, clover leaf test - CLT, Nitrocefin disk, and in vitro resistance to penicillin). Results of all tests were not dependent of bacteria type (CNS or S. aureus). Several S. aureus beta-lactamase producing isolates were from the same herd. Phenotypic tests excluding in vitro resistance to penicillin showed a strong association measured by the kappa coefficient for both bacteria species. Nitrocefin and CLT are more reliable tests for detecting beta-lactamase production in staphylococci.

Os objetivos do presente estudo foram avaliar a presença/produção de beta-lactamases por ambos os métodos fenotípicos e genotípicos, verificar se os resultados são dependentes do tipo de bactéria (Staphylococcus aureus contra Staphylococcus coagulase negativa - CNS) e verificar a concordância entre os testes. Um total de 200 amostras bactérianas oriundas de 21 rebanhos distintos foram incluídos, sendo 100 CNS e 100 S. aureus. A presença/detecção de beta-lactamase foi realizada por diferentes testes (PCR, teste trevo (clover leaf test) - CLT, disco Nitrocefin e resistência in vitro à penicilina). Os resultados de todos os testes não foram dependentes do tipo de bactérias (CNS ou S. aureus). Vários isolados de S. aureus produtores de beta-lactamase eram de um mesmo rebanho. Testes fenotípicos excluindo resistência in vitro à penicilina mostraram uma forte associação medida pelo coeficiente kappa para ambas as espécies de bactérias. Nitrocefina e CLT são testes mais confiáveis para detectar a produção de beta-lactamase em estafilococos.
Detecção de beta-lactamase em Staphylococcus aureus e Staphylococcus coagulase negativa isolados de mastite bovina
Keywords: Beta-lactamase; blaZ; Staphylococcus coagulase negativa; Staphylococcus aureus; Beta-lactamase; blaZ; coagulase-negative Staphylococcus; Staphylococcus aureus